Un’antenata carismatica. La T. XXIV nell’insediamento peuceta di Jazzo Fornasiello (Gravina in Puglia – Ba) (ACME, 2021)
Since 2009 the University of Milan has carried out archaeological excavations in the Peucetian site of Jazzo Fornasiello, a rich and rural settlement at the border between the territories of Gravina in Puglia and Poggiorsini (Italy-Bari). Now the site provides us with some new insights about the crucial role played by Peucetian women in performing rituals. The paper draws attention to a funerary enclosure (room G) within the so-called “Complesso Alfa”, which was built in the second half of the 4Th century BCE exactly above an Archaic tomb (tomb XXIV). The burial belonged to an old woman supposed to have been a charismatic lady, at least judging from some special grave goods and ritual tools buried with the lady. The Peucetian community living at Jazzo Fornasiello preserved memory of the aforementioned burial which probably became the focus of a heroic cult between the 4th and the 3rd centuries BCE, also resulting in the deposition of several subadult enchytrismoi all around the lady, whether it was meant to attract the charismatic old woman’s protection on the babies or to stress special links between past, present and future within the family group.